ANALISIS EFISIENSI MANAJEMEN MODAL KERJA TERHADAP PROFITABILITAS PT. PUSRI PALEMBANG SEBELUM DAN SETELAH SPIN-OFF - MARLINA WIDIYANTI; ISNURHADI .; PURWANTO . (JURNAL MANAJEMEN DAN BISNIS SRIWIJAYA, 2014)
The objectives of this research are to determine the effect of the current ratio (current ratio-CR), accounts receivable turnover (turnover Receivable-RTO), inventory turnover (Inventory turnover-ITO) and working capital turnover (Working capital turnover - WCTO) to profitability (Return on assets - ROA) PT. Pusri Palembang. The population of this research is the data monthly financial report period 2009-2012. Sampling method used was purposive sampling. The data analysis technique used is multiple linear regression. The results of the study showed that partial variable current ratio and the receivables turnover has no effect on profitability (ROA) while inventory turnover and working capital turnover has a positive effect on profitability (ROA). While the results of the study showed that the variables simultaneously CR, RTO, ITO and WCTO significant positive effect on profitability (ROA) with the R-square coefficient of determination (R2) of 0.763. This means that 76.3% of the dependent variable, namely ROA is affected by the independent variable CR, RTO, ITO and WCTO, while the remaining 23.7% is influenced by other factor.